CORRIGENDUM to Four Thrombotic Events Over 5 Years, Two Pulmonary Emboli and Two Deep Venous Thrombosis, When Testosterone-HCG Therapy Was Continued Despite Concurrent Anticoagulation in a 55-Year-Old Man With Lupus Anticoagulant (SAGE Publishing, 2017)
Owing to errors made by the authors, Charles J. Glueck, Kevin Lee, Marloe Prince, Vybhav Jetty, Parth Shah, and Ping Wang, the following article contains errors. Glueck CJ, Lee K, Prince M, et al. Four Thrombotic Events Over 5 Years, Two Pulmonary Emboli and Two Deep Venous Thrombosis, When Testosterone-HCG Therapy Was Continued Despite Concurrent Anticoagulation in a 55-Year-Old Man With Lupus Anticoagulant. J Investig Med High Impact Case Rep. 2016;4(3):1-6. doi: 10.1177/2324709616661833